Investigating dust trapping in transition disks with millimeter-wave polarization - Pohl, Adriana; Kataoka, Akimasa; Dullemond, Cornelis (Astronomy and astrophysics, 2016)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics